2018
DOI: 10.1097/psy.0000000000000628
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Odds of High Allostatic Load in Puerto Rican Adults: The Role of Participation in the Supplemental Nutrition Assistance Program During 5 Years of Follow-Up

Abstract: FI is associated with dysregulated components of the primary AL system, and this relationship may be stronger for those not receiving SNAP. Research is needed in additional populations to test AL as a plausible pathway connecting FI to chronic disease and SNAP as a moderator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 69 publications
1
32
0
4
Order By: Relevance
“…Further, it is possible that NFD in an observational setting is a marker of another unassessed risk factor for cardiometabolic disease such as food insecurity. NHANES data demonstrate that 22% of Hispanic households vs. 14% of all US households are food insecure [ 28 ], and food insecurity has in turn been associated with elevated cardiometabolic risk in this population [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is possible that NFD in an observational setting is a marker of another unassessed risk factor for cardiometabolic disease such as food insecurity. NHANES data demonstrate that 22% of Hispanic households vs. 14% of all US households are food insecure [ 28 ], and food insecurity has in turn been associated with elevated cardiometabolic risk in this population [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one other study has examined the association between food insecurity and allostatic load. Among 733 Puerto Rican adults in the Boston Puerto Rican Health Study (BPHC), McClain and colleagues found that food insecurity was associated with greater dysregulation of the neuroendocrine and immune systems over a five-year follow-up period, but not with the total allostatic load [42]. The differences in these findings may be due to BPHC study participants being older and already having higher burden of chronic disease at baseline than the general NHANES population, and the lack of neuroendocrine markers within NHANES to investigate this specific association.…”
Section: Discussionmentioning
confidence: 99%
“…Household food insecurity is both a form of socioeconomic adversity and an issue with relatively high prevalence in low-income and minority racial/ethnic households [1]. However, its relation to allostatic load has only been explored in one study [42]. In an analysis of 733 Puerto Rican adults residing in Boston, food insecurity was associated with greater dysregulation of the neuroendocrine and inflammatory systems, but not total allostatic load [42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore aimed to evaluate pre- and post-ARRA SNAP expansion differences in FI and dietary intake among a longitudinal cohort of Puerto Rican adults living in the mainland U.S., a population with a high prevalence of FI (7) and SNAP participation, (8) as well as poor nutrient intake, (9) and diet quality, (10) along with high rates of chronic disease. (11,12) Findings may help inform improved policy strategies that better equip Puerto Ricans and similar high-risk populations to lower FI and consume a healthy diet.…”
Section: Introductionmentioning
confidence: 99%